The Improvement of Managerial Capacity of MSMEs in Facing Global Competition - Junaidi, Junaidi; Parela, ⁠Epi; Ariswandy, David (Devotion: Journal Corner of Community Service, 2025)
This study examines the role of managerial capacity in enhancing the competitiveness of Small and Medium Enterprises (SMEs) in the global market. It highlights the importance of key factors such as financial literacy, strategic planning, leadership development, and digital adoption in improving SMEs' operational efficiency, market expansion, and long-term sustainability. Through a combination of survey data and case studies, the research identifies both the benefits and barriers of capacity-building initiatives, revealing that SMEs with structured management frameworks and access to training programs are more resilient and adaptable to market changes. The study concludes that continuous investment in managerial skills development is crucial for SME growth and economic contribution, recommending policy interventions and collaborative efforts between government, academia, and the private sector to strengthen SME competitiveness.